Illuminated manuscripts - Hayman, Richard 1959- (Shire Publications, 2017)
"Illuminated manuscripts are among the most beautiful, precious and mysterious works of Western art. Before the printing press was invented, books were produced by hand and their illustration, using brightly colored pigments and gold embellishments, was a labor of love and an act of piety in itself. ... 'Illuminated Manuscripts' describes the origin and history of medieval illumination, covering the artists and their techniques and the patrons who commissioned them. It explains the subject matter found in medieval works, such as saints and Bible stories and the use of ornamental flourishes, and is illustrated with many fine examples of the genre including the Book of Kells and the Belles Heures of the Duc de Berry." --
Keywords: Herstellung; Typologie; Geschichte; Illuminierte Handschrift; Illumination of books and manuscripts / History; Illumination of books and manuscripts, Ancient; Illumination of books and manuscripts, Medieval; Books / History / 400-1450; Books; Illumination of books and manuscripts; 400-1450; History